(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In article in the comparative plan the reasons and ways of comprehension of the phenomena of the validity surrounding the person by means of artistic images speak. In work it is underlined, that earlier the folklore was investigated separately from religion in this connection there was an indispensability of their comprehensive studying mythopoetic contents, unities and interoperability. The author proves, that the national folklore is necessary for considering in a context of development and progress of religious views and doctrines, proves a urgency of this problem in a modern science.